Financial option insurance - Wang, Qi-Wen (2017)
The option is a financial derivative, which is regularly employed in reducing the risk of its underlying securities. However, investing in options is still risky. Such risk becomes much more severe for speculators who utilize options as a means of leverage to increase their potential returns. In order to mitigate risk on their positions, the rudimentary concept of financial option insurance is introduced into practice. Two starkly dissimilar concepts of insurance and financial options are integrated into the formation of financial option insurance. The proposed financial product insures investors’ option premiums when “misfortune” befalls them. As a trade-off, they are likely to sacrifice a limited portion of their potential profits. The “loopholes” of the prevailing financial market are addressed and the void is filled by introducing a stable three-entity framework. Moreover, a specifically designed mathematical model is proposed. It consists of two portions: the business strategy of matching and a verification-and-modification process. The proposed model enables the option investors with calls and puts of different moneyness to be protected by the issued option insurance. Meanwhile, it minimizes the exposure of the option insurer’s position to any potential losses.